A self-binding immune complex vaccine elicits strong neutralizing responses against herpes simplex virus in mice - Diamos, Andrew G.; Pardhe, Mary D.; Bergeman, Melissa H.; Kamzina, Aigerim S.; DiPalma, Michelle P.; Aman, Sara; Chaves, Artemio; Lowe, Kenneth; Kilbourne, Jacquelyn; Hogue, Ian B.; Mason, Hugh S. (Frontiers in Immunology, 2023)
It has been known for over half a century that mixing an antigen with its cognate antibody in an immune complex (IC) can enhance antigen immunogenicity. However, many ICs produce inconsistent immune responses, and the use of ICs in the development new vaccines has been limited despite the otherwise widespread success of antibody-based therapeutics. In this study, we evaluated the immunogenicity of a recombinant immune complex (RIC) targeting herpes simplex virus 2 (HSV-2) glycoprotein D (gD) which was designed to generate larger multimeric complexes via self-binding. The RIC enhanced C1q receptor binding 25-fold compared to a traditional IC that was unable to form larger complexes. After immunization of mice, the RIC elicited up to 1,000-fold higher gD-specific antibody titers compared to traditional IC, reaching endpoint titers of 1:500,000 after two doses without adjuvant. The RIC construct also elicited stronger virus-specific neutralization against HSV-2, as well as stronger cross-neutralization against HSV-1, although the proportion of neutralizing antibodies to total antibodies was somewhat reduced in the RIC group. Based on these findings, further improvements to the RIC system are discussed. Overall, this work demonstrates that the RIC system overcomes many of the pitfalls of traditional IC, providing potent immune responses against HSV-2 gD. RIC have now been shown to be capable of inducing potent immune responses to a variety of viral antigens, underscoring their broad potential as a vaccine platform.